(3GdCQHYhf aj JUMjM GdeYGedIs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s ((3GdSjO GdMSf Hf GdMSjf Hf YR GdOjf Hf GdMSf GdTGei GdOGYi GdgGOhi s)
(3ChdgG (B:s
(3GdMeO ddg fGUQ Ojfg CeG HYO aEf Gddg SHMGfg LYd eMeOkG fHjg NGJe CfHjGFg hHebJVi gPg GdCNHGQCKHJfG ai gPG GdeNJUQ CQHYjf HGHkG ef JUMjM GdeYGedI s
(3BNQgG (B:s
(3hef CUGH eGdkG MQGekG hcGf ecGKQkG heaGNQkG heQGFjkG dbi Gddg YR hLd hgh Ydjg ZVjGf JeJ GdCQHYhf MOjKkG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B15 - (3U(B21s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJ GdfSNI HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
Keywords: (3GdMOjK h GdeUWdMs